Assessing the long-distance repellency of long-lasting insecticide netting to a suite of post-harvest insects - Alonso, Alicia Amairani; Wilkins, Rachel; Morrison III, William R. (My University, 2018)
Insects are our main competitors for food on the planet (1). In fact, growers lose 10-30% of crops during storage, processing, and marketing after harvest each year to stored product insects (2,3). Challenges to current management include increasing insecticide resistance to phosphine (4), which is the most common insect fumigant. Another challenge has been an increasing demand for organic or low insecticide-input products by consumers (5). To meet these challenges we came up with an alternative management approach, a long lasting insecticide netting (LLIN). Insecticide-treated nets have been widely used as a tool for malaria vector control in tropical regions since the early 1990s (6). These nets are typically treated with a pyrethroid insecticide, such as permethrin or deltamethrin, which repel, incapacitate, and kill mosquitoes that land on the nets. Researchers have recently begun exploring the use of LLINs for management of agricultural pests in high value specialty crops (7). More recently, work with LLINs in post-harvest settings has demonstrated that this tool can induce mortality, as well as significantly decrease the movement and dispersal capacity of post-harvest insects (8). Some possible uses for LLIN include being used to line windows, vents, eaves, or other openings into food facilities. However, anecdotal evidence from IPM practitioners has suggested that pyrethroids, which the LLIN contains, may be repellent to specific groups of insects. In order for LLIN to be an effective tool at intercepting and preventing infestation by stored product insects, we must demonstrate that the netting is not repellent to a range of post-harvest insects.
Keywords: Fall 2018